Failure of protein to improve time trial performance when added to a sports drink - van Essen, M.; Gibala, M. J. (Medicine & Science in Sports & Exercise, 2006)
Introduction: Recent studies have reported that adding approximately 2% protein to a carbohydrate sports drink increased cycle endurance capacity compared with carbohydrate alone. Howver, the practical implications of these studies work are hampered by the following limitations: (a) the rate of carbohydrate ingestion was less than what is considered optimal for endurance performance, and (b) the performance test (exercise time to fatigue) did not mimic the way in which athletes typically compete (i.e., a race in which a fixed distance or set amount of work is performed as quickly as possible).